UPAYA MENINGKATKAN KECERDASAN EMOSIONAL SISWA DENGAN MENGGUNAKAN MODEL DEBATE PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 3 SUMELAP - Rengganis; Febri Fajar Pratama; Rizki Hadiwijaya Zulkarnaen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to enhance the emotional intelligence of fifth-grade students atSDN 3 Sumelap by implementing a debate learning model in Pancasila Education.Emotional intelligence is considered a crucial aspect of student characterdevelopment, encompassing self-awareness, self-control, motivation, empathy,and social skills. The research method used was Classroom Action Research(CAR), implemented in two cycles, each encompassing planning, implementation,observation, and reflection. Data were collected through observation, interviews,and documentation, and analyzed qualitatively and quantitatively. The resultsshowed that the use of the debate model significantly improved studentsemotional intelligence, as indicated by increased active participation, ability toexpress opinions, and emotional control during the learning process. Therefore,the debate model can be used as an effective alternative learning strategy toimprove students emotional intelligence in Pancasila Education.